Rynkowe instrumenty finansowe a ochrona środowiska - Doś, Anna (Market Financial Instruments and Protection of the Environment, 2007)
Ecologization of the economy is nowadays initiated and sustained by the state policy. Some changes that take place at the financial market (drive by ecological factor) lead to creating new instruments (or new kinds of instruments) and new criterion of making financial decisions. As the manifestation of these changes might be acknowledged: the Social Responsible Investment, ecodeposits and ecological accounts, changes in the procedure of giving a credit, ecological insurance and new derivatives. Phenomena mentioned above have their influence on access to capital, capital cost and operational cost of business activity. At present, it is not possible to declare if described changes lead to ecologization of production. It depends on the relations between marginal cost of cleaning production and marginal cost of running an enterprise which are provoked by these changes. However, it is possible to notice that described changes are the symptom of development of the financial system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 92-106